PERBANDINGAN TINGKAT KESEGARAN JASMANI SISWA KELAS X SMA NEGRI 1 RENGAT BARAT DENGAN SISWA KELAS X SMA NEGRI 2 RENGAT BARAT - Dede suryana; Saripin '; Kristi agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem in this study began from the observation researchers that differences in physical fitness grade X SMA Negeri 1 West Rengat higher than the grade X SMAN 2 West Rengat, It can be seen during the process of teaching and learning a sport where there are still many children who complain in physical activity. Therefore, this study aimed to compare the physical fitness level of grade X SMA Negeri 1 West Rengat with grade X SMAN 2 West Rengat. This type of research is an ex post facto research. The population in this study were students of SMA Negeri 1 West Rengat consisting of 160 students and students of grade X SMAN 2 West Rengat consisting of 128 students of grade X. Sampling was done by purposive sampling, the sample in this study grade X.1 students of SMA 1 West Rengat totaling 29 people and grade X.1 students of SMA Negeri 2 West Rengat totaling 29 people, after the data is obtained, the technique of data analysis in this research is to use the test "t". From these results it could be concluded: 1) Data from tests of physical fitness grade X SMA Negeri 1 West Rengat showed a population of normal distribution, 2) Data from tests of physical fitness grade X SMAN 2 West Rengat showed a population of normal distribution, 3) Data physical fitness test results of boys and girls SMA Negeri 1 West Rengat overall average physical fitness test scores of students of SMA Negeri 1 West Rengat ie 13.28 = 13, according to the norms of physical fitness that are in the 10-13 grades Less gradeification, 4 ) the result of physical fitness test boys and girls SMAN 2 West Rengat overall average physical fitness test scores of students of SMA Negeri 2 West Rengat ie 12.53 = 13, according to Norma physical freshness grades 10-13 are in the gradeification of Less , 5) There is no comparison of the level of physical fitness among male students SMA Negeri 1 West Rengat with male student SMAN 2 West Rengat after t test obtained tcount (0.496) <t table (1.703), where Ha is rejected, 6) There is a comparison of the level of freshness physical between female student SMAN 1 West Rengat with female student SMAN 2 West Rengat West after t test obtained tcount (1.768)> t table (1.703), where Ha is accepted. Keywords: Physical Fitness level of grade X SMA Negeri 1 West Rengat with grade X SMAN 2                  West Rengat